Arthropods inhabiting flowering non-crop plants and adaptive vegetables planted around paddy fields of freshwater swamps of South Sumatra, Indonesia - Siti Herlinda; TILI KARENINA; CHANDRA IRSAN; YULIA PUJIASTUTI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Herlinda S, Karenina T, Irsan C, Pujiastuti Y. 2019. Arthropods inhabiting flowering non-crop plants and adaptive vegetables planted around paddy fields of freshwater swamps of South Sumatra, Indonesia. Biodiversitas 20: 3328-3339. Local farmers in freshwater swamps of South Sumatra traditionally plant adaptive flowering vegetables surrounding paddy fields and let wild flowering plants or non-crop plants grow on the embankment. This research aimed to determine the species of non-crop plants and adaptive vegetables surrounding the freshwater swamp paddy fields as habitats and niches of arthropods. This study used four species of flowering non-crop plants (Zinnia sp., Tagetes erecta, Cosmos caudatus, Sesamum indicum) and four species of vegetables (Vigna unguiculata, Momordica charantia, Cucumis sativus, Luffa acutangula) planted around the paddy fields. While the arthropods were collected using sweep nets. There were 24 species of predatory arthropods, three species of parasitoids, 17 species of herbivores, and nine species of neutral insects found in the non-crop plants and vegetables. The non-crop plant and vegetable species that were the most chosen by the predatory arthropods were Zinnia sp. and M. charantia, respectively. Species of the non-crop plants and vegetables chosen by the parasitoids were T. erecta and M. charantia, respectively. Those non-crop plants and adaptive vegetables were also the most chosen plants by the predatory arthropods for their habitats and niches. Therefore, for the conservation of natural enemies, it is better to use Zinnia sp., T. erecta, and M. charantia.